DESIGN OF ROADS - Axatova Kamola Shuxratovna (Scholar Express Journals, 2021)
The purpose of our highway design is all for the free movement and safety of vehicle will improve the roads based on a number of projects based on needs.
Keywords: Transport systems, materials, soils, gravel, slopes, highway project